Socialization of the Impact Arising from the Use of the Tiktok Application for School Children at SD Negeri 040443 Kabanjahe for Academic Year 2022/2023 - Juwita Tindaon; Elisabeth Ruthana Lasmaria Sinaga; Veronika Br. Sembiring; Amelia Nina Coryana Br. Panjaitan; Kelaranta Br. Depari (Jurnal Pengabdian Masyarakat Bestari, 2023)
The tiktok application has a big impact on the development of children's character, it is not uncommon for this application to have a negative impact on children, for example they often dance alone without being controlled. The period of child development that is very sensitive is at the age of 5-12 years, as in early childhood, so it is often called the golden age (Titik Mukarromah, 2019). At this time all aspects of intelligence development, namely intellectual, emotional, and spiritual intelligence experienced extraordinary developments that would influence and determine further developments (Muhibbin Syah, 2003). When a child is at the golden age, all information will be absorbed quickly. They become reliable imitators, they are smarter, smarter than they look and will form the basis for the formation of their character, personality and cognitive abilities. So you shouldn't underestimate children at that age.